2015
DOI: 10.1186/s40643-014-0033-5
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced production of flavonoids by methyl jasmonate elicitation in cell suspension culture of Hypericum perforatum

Abstract: Background: Flavonoids of Hypericum perforatum are important secondary metabolites which have been widely utilized in medicine for a range of purposes. The use of methyl jasmonate (MeJA) elicitation for the enhancement of flavonoid production in cell suspension culture of H. perforatum would be an efficient alternative method for the flavonoid production. Results: MeJA influenced the cells growth and flavonoid production. The optimal elicitation strategy was treatment of the cell cultures with 100 μmol/L MeJA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(76 citation statements)
references
References 38 publications
5
58
0
5
Order By: Relevance
“…A decline in CAT activity under CHI elicitation suggested a possible delay in removal of toxic peroxides, which could lead to a higher ROS accumulation resulting in a stimulation of phenylpropanoid and naphtodianthrone production. Such an observation is in agreement with the theory of ROS-mediated accumulation of naphtodianthrones (Danova et al 2012) and flavonoids (Wang et al 2015) in Hypericum in vitro cultures. When antioxidant enzymes in PEC elicited cells were compared, it was observed that higher CAT activity was more prolonged than that of POD.…”
Section: Antioxidant Activity Of H Perforatum Cell Suspensionssupporting
confidence: 87%
“…A decline in CAT activity under CHI elicitation suggested a possible delay in removal of toxic peroxides, which could lead to a higher ROS accumulation resulting in a stimulation of phenylpropanoid and naphtodianthrone production. Such an observation is in agreement with the theory of ROS-mediated accumulation of naphtodianthrones (Danova et al 2012) and flavonoids (Wang et al 2015) in Hypericum in vitro cultures. When antioxidant enzymes in PEC elicited cells were compared, it was observed that higher CAT activity was more prolonged than that of POD.…”
Section: Antioxidant Activity Of H Perforatum Cell Suspensionssupporting
confidence: 87%
“…The increased synthesis of flavonoids due to JA supplementation supports the findings by Horbowicz et al (2011), Ishihara et al (2002, and Wang et al (2015). Xu et al (2006) have reported that NO production induces the synthesis of JA, SA, and secondary metabolites, thereby mediating the regulated crosstalk between JA, SA, secondary metabolites, and NO signaling, for better stress amelioration.…”
Section: Discussionsupporting
confidence: 71%
“…The contents of rutin, quercetin myricetin, hesperidin, formononetin, biochanin A, kaempferol, and naringenin were higher in the JA, SA, and PGR cell cultures than in the control cell cultures. Flavonoid content was stimulated by MeJA and SA induction, which were 2.1 and 1.5 times higher when compared with the control cell suspension cultures of Hypericum perforatum [35]. The levels of pyrogallol, resveratrol, veratric acid, and vanillin were higher in the JA, SA, and PGR cell cultures than in the control cell cultures (Table 1).…”
Section: Resultsmentioning
confidence: 99%